EWSR1::POU2AF3(COLCA2) Sarcoma: An Aggressive, Polyphenotypic Sarcoma With a Head and Neck Predilection - Koshyk, Olena; Dehner, Carina A; van den Hout, Mari F C M; Bempt, Isabelle Vanden; Sciot, Raf; Huang, Hsuan-Ying; Agaimy, Abbas; Din, Nasir Ud; Klubíčková, Natálie; Mosaieby, Elaheh; Skálová, Alena; Michalová, Květoslava; et al. (Modern pathology, 2023)
EWSR1::POU2AF3 (COLCA2) sarcomas are a recently identified group of undifferentiated round/spindle cell neoplasms with a predilection for the head and neck region. Herein, we report our experience with 8 cases, occurring in 5 men and 3 women (age range, 37-74 years; median, 60 years). Tumors involved the head/neck (4 cases), and one each the thigh, thoracic wall, fibula, and lung. Seven patients received multimodal therapy; 1 patient was treated only with surgery. Clinical follow-up (8 patients; range, 4-122 months; median, 32 months) showed 5 patients with metastases (often multifocal, with a latency ranging from 7 to 119 months), and 3 of them also with local recurrence. The median local recurrence-free and metastasis-free survival rates were 24 months and 29 months, respectively. Of the 8 patients, 1 died of an unknown cause, 4 were alive with metastatic disease, 1 was alive with unresectable local disease, and 2 were without disease. The tumors were composed of 2 morphologic subgroups: (1) relatively bland tumors consisting of spindled to stellate cells with varying cellularity and fibromyxoid stroma (2 cases) and (2) overtly malignant tumors composed of nests of "neuroendocrine-appearing" round cells surrounded by spindled cells (6 cases). Individual cases in the second group showed glandular, osteogenic, or rhabdomyoblastic differentiation. Immunohistochemical results included CD56 (4/4 cases), GFAP (5/8), SATB2 (4/6), keratin (AE1/AE3) (5/8), and S100 protein (4/7). RNA sequencing identified EWSR1::POU2AF3 gene fusion in all cases. EWSR1 gene rearrangement was confirmed by fluorescence in situ hybridization in 5 cases. Our findings confirm the head/neck predilection and aggressive clinical behavior of EWSR1::POU2AF3 sarcomas and widen the morphologic spectrum of these rare lesions to include relatively bland spindle cell tumors and tumors with divergent differentiation.
Keywords: senioři; spindle cell sarcoma; RNA-Binding Protein EWS; hybridizace in situ fluorescenční; Sarcoma; protein EWS vázající RNA; sinonasal tract; Middle Aged; mužské pohlaví; Adult; nádory měkkých tkání; Calmodulin-Binding Proteins; RNA-Binding Proteins; In Situ Hybridization, Fluorescence; Biomarkers, Tumor; ženské pohlaví; nádorové biomarkery; Humans; gene fusion; EWSR1::POU2AF3; sarkom; proteiny vázající RNA; lidé středního věku; sarcoma; proteiny vázající kalmodulin; Soft Tissue Neoplasms; neuroendocrine-like; soft tissues; dospělí; COLCA2; Female; Aged; lidé; Male